The Quantitative Implications of Definitions of Giftedness - Matthew T. McBee; Matthew C. Makel (SAGE Publishing, 2019)
Educational psychology is replete with verbal or qualitative definitions through which students can be considered members of categories, such as learning disabled, autistic, or gifted. These conceptions carry quantitative implications regarding the incidence rates of the phenomena they describe. To be scientifically useful, such definitions should have sufficient specificity and internal consistency. We analyzed four influential definitions of giftedness and assessed their internal consistency by computing the giftedness rate implied by each. Results reveal that the proportion of individuals who meet the standard of giftedness under some definitions is unrealistically high (e.g., >75% in some conditions). The implication of this work is that the rigor and internal self-consistency of educational concepts requires improvement. The field must carefully consider the quantitative implications of its concepts, statements, and definitions. An Open Science Framework project page containing R code, a technical appendix, and all figures and tables from this paper is available at https://osf.io/6e7g9/ .